2007
DOI: 10.1249/mss.0b013e31802dd3e6
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Critical Power Using a 3-min All-out Cycling Test

Abstract: During a 3-min all-out cycling test, power output declined to a stable value in approximately the last 45 s, and this power output was not significantly different from the independently measured critical power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
434
10
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 274 publications
(478 citation statements)
references
References 29 publications
31
434
10
3
Order By: Relevance
“…O 2 and perturbation of pH, [Pi] and [PCr] , Poole et al, 1988. In support of this, CS has been shown to occur in close proximity to maximal lactate steady state (MLSS) (Smith and Jones, 2001 The availability of a single test to determine the parameters of the speed-time relationship would facilitate use of the relationship by reducing the number of testing sessions necessary, as the all-out test has done for other modes of exercise (Burnley, 2009, Cheng et al, 2012, Vanhatalo et al, 2007. For example, a single test would be more practical in the athletic arena, so as to minimize any disruption to a training schedule.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…O 2 and perturbation of pH, [Pi] and [PCr] , Poole et al, 1988. In support of this, CS has been shown to occur in close proximity to maximal lactate steady state (MLSS) (Smith and Jones, 2001 The availability of a single test to determine the parameters of the speed-time relationship would facilitate use of the relationship by reducing the number of testing sessions necessary, as the all-out test has done for other modes of exercise (Burnley, 2009, Cheng et al, 2012, Vanhatalo et al, 2007. For example, a single test would be more practical in the athletic arena, so as to minimize any disruption to a training schedule.…”
Section: Discussionmentioning
confidence: 96%
“…For cycling, 3-min is adequate time to allow for the complete depletion of W` and a leveling off in power output equal to CP (Burnley et al, 2006, Vanhatalo et al, 2007. It has recently been demonstrated that 3-min is also adequate time for an all-out rowing test (Cheng et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations